Migrating to Australia good meh??? - Soong, Ken; Soong, Michael (Gerakbudaya Enterprise, 2013)
Migrating to Australia, Good Meh? by Michael and Ken Soong, two brothers that have been living in Australia for quite some time. This book presents the bitter sweet (and sour) truth based on the authors' experiences as Malaysian migrants living in Australia - from the perspectives of not only Malaysians but also South East Asians; about the so called more 'equal' opportunities, advanced, liberal, democratic, laissez-faire ways of life in the land of Australia which supposed to be better than Malaysia in any way and every respect! Is Australia all rosy, nice, and dandy? The short answer is 'yes' and 'no'. The long answer is not too long either as you can see the book is not a thick one at all. While this book is not some sort of a 'one size fits all' instruction manual of migrating and living in Australia, the authors do believe it contains some noteworthy discussions and anecdotal accounts that can shed light on the dilemmas, ironies, opportunities, challenges, hopes, despair, frustration, excitements, and emotions.